MEDICAL AND NEUROLOGICAL REHABILITATION OF PATIENTS AFTER ILLNESS - Muxamedova Zarifa Ramazonovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract The problem has been studied extremely insufficiently, and in the literature there are isolated works in which only general assessments of the dynamics of individual motor and emotional (depression) disorders in males and females who have had a cerebral stroke are given. These issues require further study, since Based on the above characteristics, the approaches to the tactics of rehabilitation treatment after stroke in males and females should be different. According to special studies, hemispheric functional differences are explained in terms of morphological and biochemical characteristics of the right and left hemispheres in persons of different sexes. At the same time, the issues of interhemispheric asymmetry and the features of the functional relationships of the hemispheres in cerebral strokes remain practically unexplored.